Methodology for Measuring the Customer Satisfaction with the Logistics Services - Stopka, Ondrej; Černá, Lenka; Zitrický, Vladislav (Naše more znanstveni časopis za more i pomorstvo, 2016)
The article deals with the proposal of methodology for measuring the customer satisfaction with the logistics services. The methodology reflects mostly the subjective quality evaluation which is based on the directly and indirectly measurable characteristics. Researched characteristics result from the customer feelings, wishes, requirements and the experiences of experts which studied the answers from the questionnaire survey. Answers from the questionnaire survey evaluate the quality of logistics services and the importance of evaluation criteria. Objective quality evaluation is verified by the methods for measuring the customer satisfaction. These methods for determining the weights of selected criteria ware verified on the basis of proposed flowchart as well.